Tumor DNA From Tumor In Situ Fluid Reveals Mutation Landscape of Minimal Residual Disease After Glioma Surgery and Risk of Early Recurrence - Yu, Jinliang; Sheng, Zhiyuan; Wu, Shuang; Gao, Yushuai; Yan, Zhaoyue; Bu, Chaojie; Gu, Jianjun; Bu, Yage; Deng, Kaiyuan; Xu, Sensen; Chen, Zhongcan; Zhang, Qianqian; et al. (Frontiers in Oncology, 2021)
The recurrence of glioma is a difficult problem in clinical treatment. The molecular markers of primary tumors after resection cannot fully represent the characteristics of recurrent tumors. Here, Abundant tumor DNA was detected in tumor in situ fluid (TISF), we report that TISF derived tumor DNA (TISF-DNA) can detect genomic changes in recurrent tumors and facilitate recurrence risk analysis, providing valuable information for diagnosis and prognosis. The tumor DNA in TISF is more representative and sensitive than that in cerebrospinal fluid. It reveals the mutational landscape of minimal residual disease after glioma surgery and the risk of early recurrence, contributing to the clinical management and clinical research of glioma patients.